2007
DOI: 10.1016/j.matbio.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure and embryonic expression of zebrafish lysyl hydroxylase 1 and lysyl hydroxylase 2

Abstract: Collagen biosynthesis in both invertebrates and vertebrates is critically dependent upon the activity of lysyl hydroxylase (LH) enzymes. In humans, mutations in the genes encoding LH1 and LH2 have been shown to cause two distinct connective tissue disorders, Ehlers-Danlos (Type VIA) and Bruck syndromes. While the biochemical properties of these enzymes have been intensively studied, their embryonic patterns of expression and developmental roles remain unknown. We now present the cloning and analyses of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Three LH isoforms, LH1, LH2a/2b and LH3, originating from three different genes, have been characterized so far from human, mouse, rat and zebrafish [13][14][15][16][17][18][19][20][21]. We have demonstrated that LH3 and C. elegans LH, the only ortholog for lysyl hydroxylase in the nematode, are multi-functional enzymes possessing LH, GT and GGT activities in vitro [21][22][23][24].…”
Section: Introductionmentioning
confidence: 94%
“…Three LH isoforms, LH1, LH2a/2b and LH3, originating from three different genes, have been characterized so far from human, mouse, rat and zebrafish [13][14][15][16][17][18][19][20][21]. We have demonstrated that LH3 and C. elegans LH, the only ortholog for lysyl hydroxylase in the nematode, are multi-functional enzymes possessing LH, GT and GGT activities in vitro [21][22][23][24].…”
Section: Introductionmentioning
confidence: 94%
“…At the molecular level, both processes are regulated by the expression of apoptotic-or regeneration-associated genes. 23 However, it is still under debate whether regenerating axons rely on environmental cues to guide them toward their original target 27 and which cues are responsible for this process.…”
mentioning
confidence: 99%
“…In the brain, on the other hand, only a small amount was detectable and was located intracellularly in the pyramidal cells, while its specific role remains unknown. 25,26 Regarding zebrafish, apart from lh3 being expressed in the peripheral glia, corresponding temporally with motor axon outgrowth, 27 we are not aware of a role in the central nervous system (CNS).…”
mentioning
confidence: 99%
“…Three lysyl hydroxylase isoforms (LH1, LH2, and LH3) have been identified from human, mouse, rat, and zebrafish (3)(4)(5)(6)(7)(8)(9)(10). In addition, LH2 has two alternatively spliced forms, LH2a (short) and LH2b (long) (11).…”
mentioning
confidence: 99%